Liquid-Phase Synthesis of Nano-Zinc Oxide and Its Photocatalytic Property - Rong Wang (International Journal of Analytical Chemistry)
To solve the problem of liquid-phase synthesis of nano-ZnO, a photocatalytic performance study was proposed. In this study, the microwave homogeneous precipitation method was used to add different types and amounts of surfactants. The synthesis of nano-zinc oxide was controlled by changing the reaction system conditions. The photocatalytic properties of nano-zinc oxide for degrading three water-soluble dyes were preliminarily studied and discussed. The results show that the photocatalytic performance of nano-ZnO is closely related to its size, morphology, specific surface area, and even crystallographic direction.